Genotypes of ANKK1 and DRD2 genes and risk of metabolic syndrome and its components: A cross-sectional study on Iranian women. Issue 5 (September 2021) - Aliasghari, Fereshteh; Mahdavi, Reza; Barati, Meisam; Nazm, Saba A.; Yasari, Sepideh; Bonyadi, Mortaza; Jabbari, Masoumeh
Abstract: We aimed to investigate the association between polymorphism of DRD2/ANKK1 gene with MetS and its components. Women (n = 531, aged 19–50 years) from the North-west of Iran were included by cluster sampling method. Polymorphisms of ANKK1 and DRD2 genes were defined in the study population. D/D (OR: 3.16; 95%CI: 1.31−7.60) and I/D (OR: 1.76; 95%CI: 1.12−2.78) genotypes of DRD2 (rs1799732) increased risk of MetS compared to I/I genotype. The D/D genotype of DRD2 (rs1799732) increased odds of hypertriglyceridemia in the study population. T/T (OR: 6.72; 95%CI: 1.99−22.71) and C/T (OR: 4.42; 95%CI: 2.79−7.01) genotypes of ANKK1 (rs1800497) increased risk of MetS compared to C/C genotype. Also, C/T genotype increased the odds of HTN, high FBS, high TG and low HDL-C levels compared to C/C genotype. These polymorphisms can affect the MetS components via their relation to the signaling of dopaminergic pathways and eating behaviors.